Physicochemical properties and consumer preference of imitation chicken nuggets produced from chickpea flour and textured vegetable protein - Sharima-Abdullah N.; Hassan C.Z.; Arifin N.; Huda-Faujan N. (Universiti Putra Malaysia, 2024)
Indexed by WOS/SCOPUS/ERA